Structural style and its impact on trapformation and hydrocarbon distribution in Muglad rift basin, Sudan / Ali Abd Elkaream Omer - Ali Abd Elkaream , Omer (2017)
Muglad Basin is recognized to be a major part of Sudanese interior rift basins. It’s one of the main products of Central African Shear zone. It is characterized by thick non-marine clastic sequences of Late Jurassic /Early Cretaceous to Tertiary age. More than 15 km of sedimentary section have been inferred from seismic data in the main trough. Three major rifting episodes are documented in the basin. The first rifting event is estimated to have occurred in Late Jurassic/Early Cretaceous, the second in Late Cretaceous Coniacian-Santonian times and continued until the end of cretaceous and the third during Tertiary. The structural framework of the basin is controlled by two sets of faults: an approximately north-south trending set of Cretaceous faults and northwest-southeast trending Tertiary faults. The repeated faults re-activation and, possibly, an oblique extensional stress direction during the Tertiary rifting, generated complex system of extensional and transtensional rift basins. This structural complexity had significantly controlled the generation, migration and entrapment of hydrocarbon. Examples of these controls include: (a) Inversion structures formed after the main phase of oil charge would only depend on re-migrated hydrocarbon. (b) Tilted extensional fault blocks require lateral fault seal and in truncated parts of the source rock, migration is directed into the overlying reservoir and therefore this is a key exploration risk (c) faults dipping direction and throw can play some role in the lateral migration of hydrocarbon. The thermal maturity modelling for the Abu Gabra Formation indicates that in the Abu Gabra-Lower the generation of hydrocarbon reached the expulsion in the Aptian (>50% transformation ratio) and continued to present-day and the time of peak oil generation and expulsion from Abu Gabra source rocks accumulate after deposition of related seal rocks within the study area.